Multiple Moving Obstacles Avoidance of Service Robot using Stereo Vision - Widodo Budiharto; Ari Santoso; Djoko Purwanto; Achmad Jazidie (Universitas Ahmad Dahlan, 2011)
In this paper, we propose a multiple moving obstacles avoidance using stereo vision for service robots in indoor environments. We assume that this model of service robot is used to deliver a cup to the recognized customer from the starting point to the destination. The contribution of this research is a new method for multiple moving obstacle avoidance with Bayesian approach using stereo camera. We have developed and introduced 3 main modules to recognize faces, to identify multiple moving obstacles and to maneuver of robot. A group of people who is walking will be tracked as a multiple moving obstacle, and the speed, direction, and distance of the moving obstacles is estimated by a stereo camera in order that the robot can maneuver to avoid the collision. To overcome the inaccuracies of vision sensor, Bayesian approach is used for estimate the absense and direction of obstacles. We present the results of the experiment of the service robot called Srikandi III which uses our proposed method and we also evaluate its performance. Experiments shown that our proposed method working well, and Bayesian approach proved increasing the estimation perform for absence and direction of moving obstacle.